Legalization of recreational cannabis: Facilitators and barriers to switching from an illegal to a legal source - Kirsten Robertson (Elsevier, 2021)
Illicit markets persist in places where recreational cannabis has been legalized. This study aimed to identify perceived facilitators/barriers of switching from an illicit to a licit cannabis source. Using a cross-sectional qualitative approach, 529 students, from one New Zealand university, completed a survey investigating the facilitators/barriers to switching through two open-ended questions. Perceived facilitators for switching included: safety (63.1%); price (42.7%); legal, no risk of convictions (35.3%); increased accessibility (32.3%); product diversity (14.2%). Perceived barriers included: price (66.4%); judgement (36%); regulation (28.9%); loyalty to current supplier (27.2%); reduced accessibility (13.2%). The findings provide recommendations for policies aimed at tipping people in favor of a licit over an illicit source. Avoiding arrest/convictions, and easier access, were not primary facilitators for switching. Thus, providing a licit market might be insufficient in the absence of other competitive factors, such as communicating improved product safety. Competitive pricing and regulation (tetrahydrocannabinol strength/quantity limits) were also barriers. Given legal markets aimed at minimizing harm are constrained with competing in these areas, it is significant that our findings identified other barriers which could be overcome, including limiting surveillance and quantity limits and positioning stores to preserve anonymity. The findings also highlight that loyalty to current illicit suppliers will be a significant barrier.